FIELD INDUCED STUDIES IN CARBON NANOTUBES DOPED NEMATIC LIQUID CRYSTAL MIXTURE (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Carbon nanotubes (CNTs) doped nematic liquid crystal (NLC) mixture of varying concentrations of CNTs in 0.0, 0.2 and0.5 wt./wt.% ratios have been prepared and studied. The effect of electric field on current behavior and optical propertiesin pure NLC and CNTs-NLC mixtures has been investigated. Dispersion of CNTs in NLC mixture increases the currentnearly 3 times. The lower concentration of CNTs leads to better optical responses